Devlet hesabına yapılan alım, satım ve yapıma fesat karıştırma suçu (TCK. m.205) - Balcı, Murat (My University, 2004)
Devlet hesabına yapılan alım, satım ve yapıma fesat karıştırma suçu adlı tezimiz üç kısımdan oluşmaktadır. Birinci kısımda genel açıklamalar, suçun hukuki niteliği, benzer suçlarla mukayese ve tarihi gelişim incelenmiştir. İkinci kısımda ise suçun faili, mağduru, suçla korunan hukuki menfaat, suçun unsurları ve özel görünüş şekillerine değinilmiştir. Üçüncü kısımda TCK. Tasarılarındaki düzenleniş şekli, müeyyide ve kovuşturma usulü incelenerek çalışma tamamlanmıştır. THE SUMMERY OF MY THESİS İn my investigation, I searched to people who worked up guilt in the buying and sale by the state administration. Some people do bad treat in this proses. State is done something and people find a road to do bad thing. The thesis has got three parts. İn the first part is containing general explanation a bout theme, in the second part the people who do a guilt, this is a peretrator. On the other hand we see awronged. And I find aut the element of guilt, in some plases we see private guilts. I investigated this problems. The third part is containing, how do Türkish Law (TCK.) workout this theme and if people do this the law do what. I investigate thiese themes and I finished my working.
Keywords: Anayasa ve idare hukuku; Hukuk; İdare Hukuku